Custom 3D Printable Silicones with Tunable Stiffness. Issue 4 (6th December 2017) - Durban, Matthew M.; Lenhardt, Jeremy M.; Wu, Amanda S.; Small, Ward; Bryson, Taylor M.; Perez‐Perez, Lemuel; Nguyen, Du T.; Gammon, Stuart; Smay, James E.; Duoss, Eric B.; Lewicki, James P.; Wilson, Thomas S.
Abstract: Silicone elastomers have broad versatility within a variety of potential advanced materials applications, such as soft robotics, biomedical devices, and metamaterials. A series of custom 3D printable silicone inks with tunable stiffness is developed, formulated, and characterized. The silicone inks exhibit excellent rheological behavior for 3D printing, as observed from the printing of porous structures with controlled architectures. Herein, the capability to tune the stiffness of printable silicone materials via careful control over the chemistry, network formation, and crosslink density of the ink formulations in order to overcome the challenging interplay between ink development, post‐processing, material properties, and performance is demonstrated. Abstract : The capability to tune the stiffness of 3D printable silicone materials via careful control over the chemistry, network formation, and crosslink density of our ink formulations is demonstrated in order to overcome the challenging balance between ink development, post‐processing, material properties, and performance. Material applications include high‐performance foams and cellular solids, soft robots, biomedical devices and biological scaffolds, and flexible and stretchable electronics.